2001
DOI: 10.2514/2.2812
|View full text |Cite
|
Sign up to set email alerts
|

Compressible Dynamic Stall Control: Comparison of Two Approaches

Abstract: The approaches of compressible dynamic stall control using real-time airfoil adaptation and slatted airfoils are compared. Each method attempts to solve the unsteady ow separation and the underlying causes differently. The approaches lead to unexpected results: For the slatted airfoil, dynamic stall alleviation on the main airfoil with a fully stalled slat occurred, and for the shape adapting airfoil, leading-edge attached ow with trailing-edge separation was obtained. In both cases, no dynamic stall vortex wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…height) to obtain detailed information about the NACA 0012 airfoil operating under conditions that produce dynamic stall [7]. The Reynolds number was around 6x10 5 and the average dimensionless pitching frequency (k) was 0.1. The airfoil was constrained so that sinusoidal oscillations (α = 15.05° + 10.25° Sin ωt) in pitch could be imposed.…”
Section: Experimental Setup and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…height) to obtain detailed information about the NACA 0012 airfoil operating under conditions that produce dynamic stall [7]. The Reynolds number was around 6x10 5 and the average dimensionless pitching frequency (k) was 0.1. The airfoil was constrained so that sinusoidal oscillations (α = 15.05° + 10.25° Sin ωt) in pitch could be imposed.…”
Section: Experimental Setup and Instrumentationmentioning
confidence: 99%
“…Unsteady separating flows over pitching airfoils have therefore been extensively investigated [1]. Attempts have been made to manipulate the flow using various types of active flow-control devices, such as, steady blowing, periodic zero-mass-flux wall blowing and mechanically forced deformable leading edge nose [2,3,4,5]. Exter-nally driven flexible walls form another important mode of flow control.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported in Ref. 8 addresses this using a variable shape leading-edge in compressible dynamic stall, and this is an interesting candidate approach. However, the leading-edge environment on a rotor is severe, as evidenced by the use of erosion strips along most operational rotors, and flow control actuation in this region may be difficult to engineer.…”
Section: Nomenclature Amentioning
confidence: 99%
“…Unsteady separating flows over pitching airfoils have therefore been extensively investigated [1] and details of the underlying physics unraveled, especially at low Reynolds numbers. Using this knowledge attempts have been made to manipulate the flow using various types of active flow-control devices, such as, steady blowing, periodic zero-mass-flux wall blowing and mechanically forced deformable leading edge nose [2,3,4,5,6,7,8]. Externally driven flexible walls form another important mode of flow control.…”
Section: Introductionmentioning
confidence: 99%